Was a lease effective as a weapon of lordship? The use of documents in the principality of Salerno (10th-11th Century) - Nishimura, Yoshiya (Reti Medievali Rivista, 2017)
This paper attempts to examine the strategic use of the agrarian contracts by the landlords of the principality of Salerno in the tenth and eleventh centuries. The appearance and the structuralization of the lease would reflect the landlords’ will both to strengthen control over tenants and to increase revenue from their estates, imposing new conditions different from customary practices, such as terraticum. Here the case of the church of San Massimo in Salerno is examined. The church failed in increasing their portion of rent in kind, whereas they were to some extent successful in urging their tenants to improve the productivity of their land by forceful use of written contracts.